Propuesta interiorista de un centro de interacción y sociabilización para adultos en el norte de Quito - Salazar Del Pozo, Carolina (2019)
Currently in our country there are no entertainment venues exclusively for adults. For this reason, the intervention of an interaction and socialization center for adults (40-65 years) is planned in the north of the city of Quito, in the province of Pichincha, in the Barrio Benalcazar. It is an innovative proposal of change of use to generate an exclusive and ideal space where adults can share, feel useful, exchange feelings, receive emotional support and, above all, have fun with like-minded people and of the same age. With this interior design proposal you can provide a suitable space that is exclusive, private, safe, comfortable and of good category. A nice place for adult audiences to interact, socialize, take up their free time, clear their mind and get out of the routine. Adults can share and enjoy various recreational activities either with a partner or among friends.